2009
DOI: 10.1056/nejmoa0800836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumococcal Conjugate Vaccine on Pneumococcal Meningitis

Abstract: Background Invasive pneumococcal disease declined among children and adults after the introduction of the pediatric heptavalent pneumococcal conjugate vaccine (PCV7) in 2000, but its effect on pneumococcal meningitis is unclear. Methods We examined trends in pneumococcal meningitis from 1998 through 2005 using active, population-based surveillance data from eight sites in the United States. Isolates were grouped into PCV7 serotypes (4, 6B, 9V, 14, 18C, 19F, and 23F), PCV7-related serotypes (6A, 9A, 9L, 9N, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
266
2
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(301 citation statements)
references
References 23 publications
15
266
2
18
Order By: Relevance
“…The studies discussed above corroborate the hypothesis of this epidemiological shift by demonstrating benefits of dexamethasone in those patient populations with a high percentage of Hib meningitis and the absence of protective effects in pneumococcal meningitis. Besides the Hib vaccine, the introduction of the pneumococcal conjugate vaccine in the 2000s was responsible for an almost 60% decrease of cases of pneumococcal meningitis in children under 18 years, from 1998 to 2005, in a U.S. epidemiological study (32) . Therefore, it is plausible that the major contribution of prevention strategies has minimized the effectiveness of adjuvant dexamethasone and that it has lost its role in the current epidemiological context of BM in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies discussed above corroborate the hypothesis of this epidemiological shift by demonstrating benefits of dexamethasone in those patient populations with a high percentage of Hib meningitis and the absence of protective effects in pneumococcal meningitis. Besides the Hib vaccine, the introduction of the pneumococcal conjugate vaccine in the 2000s was responsible for an almost 60% decrease of cases of pneumococcal meningitis in children under 18 years, from 1998 to 2005, in a U.S. epidemiological study (32) . Therefore, it is plausible that the major contribution of prevention strategies has minimized the effectiveness of adjuvant dexamethasone and that it has lost its role in the current epidemiological context of BM in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of studies found could be explained by the large decrease in the incidence of bacterial meningitis (32) , especially in developed countries, reducing its epidemiological importance. This low incidence could also explain the existence of several studies with small samples and containing adults and children in the same group.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of IPD changed significantly after infant PCV7 vaccination program [12,14,47,48]. A population-and laboratory-based active bacterial core (ABC) surveillance system report a reduction in incidence of IPD among children aged \5 years from 99 cases per 100,000 population during 1998-1999 to 21 cases per 100,000 population in 2008 (79 % reduction) [17 •• ].…”
Section: Incidence Of Ipdmentioning
confidence: 99%
“…Following PCV7 implementation in resource-rich countries, non-PCV7 serotypes have increased among asymptomatic carriers (''serotype replacement'') [13]. Also, an increase in incidence of IPD due to non-vaccine types (especially serotype 19A) was noted in the US and several other countries in Europe and Asia-Pacific region [12,15,25,45,54]. The absolute rate increase in IPD due to serotype 19A is estimated at *5 cases per 100,000 population compared with decline in the rate of IPD due to PCV7 serotypes [55,56].…”
Section: Serotype Replacement and Emergence Of Antimicrobial Resistancementioning
confidence: 99%
“…The advent of pneumococcal vaccines provided a potential way of preventing pneumococcal infections effectively. Available pneumococcal conjugate vaccines can induce protection in children aged 2 months and are well-tolerated, decreasing considerably the incidence after their introduction as showed different studies by Clarke (2006), Tsai et al, (2008) and Hsu et al, (2009 …”
Section: Introductionmentioning
confidence: 98%